From resisting to reconnecting: Reducing employee resistance to returning to the office - Acurato, Meg C. (Animo Repository, 2022)
The COVID-19 outbreak has caused an unprecedented impact on many businesses worldwide. As a result, many organizations were forced to quickly adapt to a work-from-home setup to ensure the safety and well-being of their employees. Now that vaccines and booster shots were already distributed and infection rates are beginning to stabilize in the country, the Philippine Economic Zone Authority (PEZA) decided for all ecozone-registered firms to return to office starting April 1, 2022. Given the short notice from remote working to onsite working, there is a challenge in employee resistance to the sudden change of work arrangement. This gave me and my collaborators the idea of doing action research about addressing the issue of employee resistance to the sudden transition to onsite work. Albeit our company has been very generous in supporting employees during the work-from-home setup, it is also imperative for the company to help their workforce prepare for the return to onsite work. As stated under the Occupational Safety and Health (OSH) law, employers have a responsibility to provide safe workplaces for employees to perform their jobs. In this action research, we aimed to develop an intervention program that will help explain the reasons for returning to onsite work. Likewise, our primary goal is to prepare ourselves to return to the physical office and reduce resistance to the sudden change in work arrangement. Through the utilization of action research tools, we were able to determine that the frameworks 3-Stage Change Model by Lewin (1951), Work Adaptation Theory by Petrini and Hultman (1995), and the Three-Factor Theory by Sirota (2005) are what we need to guide us in taking actions. In spite of time limitations, the two cycles showed a significant development based on my collaborators’ feedback and the survey research conducted.